IMPROVING MATHEMATICS LEARNING OUTCOMES WITH REALISTIC MATHEMATICS LEARNING (PMR) FOR HIGH SCHOOL (SMA) STUDENTS - Ully Reza; Nazariah Nazariah; Nailul Authary (Jurnal Ilmiah Pendidikan dan Pembelajaran Matematika, 2024)
Low mathematics learning outcomes greatly influence students’ motivation in learning, the lack of mathematics learning outcomes can originate from students, teachers and the environment. Therefore, to improve mathematics learning outcomes, teachers should use realistic mathematics learning (PMR) for cclass XII MIPA 1 MAN 1 ACEH BESAR students. This research aims to improve mathematics learning autcomes by applying a realistic mathematics learning model to class XII MIPA 1 MAN 1 ACEH BESAR students. This type of research is quasi-experimental research. Data collection was carried out using tests (pretest and posttest) and questionnaires. The collected data was analyzed using quantitative analysis. The results of the research show that the pretest and posttest variables obtained were significant 0.0000.05, so H0 was rejected and Ha was accepted so that in accordance with the basis for decision making in data hypothesis testing it can be concluded that the data has a significant influence. Based on this, it can be concluded that the use of realistic mathematics learning models can improve students’ mathematics learning outcomes in permutation and combination material.